Sustaining the Philippine manufacturing sector - Intal, Ponciano Jr; Borromeo, Miguel Roberto V.; Castillo, Jesus Carlos Exequiel D. (The Philippine Review of Economics, 2008)
The Philippine manufacturing sector is an anomaly in East Asia's economic development experience in that it fails to provide the dynamic growth push the successful East Asian economies experienced. After undergoing a wrenching adjustment in the 1990s and early 2000s, the sector is likely to experience robust growth from impulses from other sectors of the economy and as its industrial restructuring process deepens and widens to industries and niches in which the country has comparative advantage.